(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To describe a radiological approach for evaluation of postmenopausal bleeding as an alternate to Diagnostic D&C. Materials and Methods: First 100 patients referred from the Dept of Obstetrics & Gynecology with postmenopausal bleeding for ultrasound evaluation and in some cases to confirm the findings of per vaginum examination. These patients later underwent Diagnostic D&C and the results were compared. Results: The results of our study showed that findings in patients with postmenopausal bleeding evaluated with USG (both grey scale and color Doppler per abdomen and per vaginal) were equivocal to Diagnostic D&C. Conclusion: Study concludes that USG is a non-invasive and safe alternate approach to invasive Diagnostic D&C.